Do CAR, Cash Ratio, OER and LDR an Effect on NPL? - Dien Noviany Rahmatika; Juli Riyanto Tri Wijaya; Prasetyo, Irwan (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2025)
This study seeks to examine the impact of Conventional Rural Credit Banks (BPR) in the Former Pekalongan Residency Area by analyzing various factors, including CAR, Cash Ratio, OER, and LDR, on NPL. This study uses quantitative data with purposive sampling method, the population is 30 Conventional BPRs and the research sample is 14 Conventional BPRs in the Ex-Pekalongan Residence Area. This data is processed using SPSS 22. This study's findings suggest that CAR and the Cash Ratio do not significantly impact NPL. However, both OER and LDR demonstrate a positive correlation with NPL. This research provides benefits for Conventional BPRs in the Pekalongan Ex-Residency Area. This study's findings deliver valuable knowledge and insights to Conventional BPRs in the Pekalongan Ex-Residency to support their credit or loan provision activities. With this research, it is hoped that Conventional BPRs will be more careful and more selective in providing credit to customers so that there are no NPLs or bad debts. The scope of this research is limited to Conventional Rural Banks (BPRs) operating within the former Pekalongan Regency between 2019 and 2023. Consequently, the findings should not be extrapolated to other regions with dissimilar characteristics